PENGEMBANGAN MEDIA KOMPONEN INSTRUMEN TERPADU (KIT) IKATAN KIMIA - Indriani, Evy; Sahputra, Rachmat; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of this research was to determine the level of feasibility and response of students to the integrated instrument component media of chemical bonding. The research method used was research and development (R&D) which adopt Borg & Gall development model. The subjects of this research was integrated instrument component media of chemical bonding which tested on the students of SMA Negeri 1 Sajad, SMA Negeri 1 Sambas, and SMA Negeri 1 Tebas. It was conducted initial field trials and main field trials of product users. The instruments used in this research was questionnaire. Based on research result, it can be concluded that the integrated instrument component media of chemical bonding is very feasible. It could be used in classroom to teach chemical bonding. According to expert, the percentage average score of graph, linguistic, and material judgement was 88,33% while student response to used this media was 81,39%.Keywords: Integrated Instrument Component Media, Chemical Bonding, Borg & Gall